Perinatal outcomes of monochorionic diamniotic triplet pregnancies: a case series - Tingting Xu; Xiaodong Wang; Haiyan Yu; Xinghui Liu (BMC, 2019)
Abstract Background Triplet pregnancies are associated with higher fetal morbidity and mortality rates as well as life-threatening maternal complications. Monochorionic diamniotic (MCDA) triplet pregnancies are very rare compared to other types of triplet pregnancies. Case presentation We report three cases of MCDA triplet pregnancies between January 2012 and December 2017. Two of these MCDA triplet pregnancies received regular and intensive prenatal care, were diagnosed by ultrasonography during the first trimester or early second trimester, and had good perinatal outcomes. The case with irregular perinatal care had poor outcomes, and the MCDA triplet pregnancy was diagnosed intrapartum. Conclusions The possibility of continuing an MCDA triplet pregnancy should be recognized. Early diagnosis, regular antenatal care, close prenatal monitoring, and sufficient communication are recommended to obtain better perinatal outcomes in MCDA triplet pregnancies.